2021
DOI: 10.3389/fcell.2021.679658
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell-Derived Exosomal miR-770 Inhibits M2 Macrophage Polarization via Targeting MAP3K1 to Inhibit the Invasion of Non-small Cell Lung Cancer Cells

Abstract: BackgroundNon-small cell lung carcinoma (NSCLC) is a type lung cancer with high malignant behaviors. MicroRNAs (miRNAs) are known to be involved in progression of NSCLC. In order to explore potential targets for the treatment of NSCLC, bioinformatics tool was used to analyze differential expressed miRNAs between NSCLC and adjacent normal tissues.MethodsBioinformatics tool was used to find potential targets for NSCLC. Cell proliferation was investigated by Ki67 staining. Cell apoptosis was measured by flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 40 publications
(41 reference statements)
0
33
0
Order By: Relevance
“…It has been well documented that M2 macrophages promote tumor growth and metastasis ( Tao et al, 2020 ). On the other hand, many studies indicated tumor cells stimulate naive M0 macrophages to differentiate into M2 macrophages ( Liu et al, 2021 ). Macrophages are mainly M2 subtypes in tumor microenvironment, especially in advanced stage of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that M2 macrophages promote tumor growth and metastasis ( Tao et al, 2020 ). On the other hand, many studies indicated tumor cells stimulate naive M0 macrophages to differentiate into M2 macrophages ( Liu et al, 2021 ). Macrophages are mainly M2 subtypes in tumor microenvironment, especially in advanced stage of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…They act as gene regulator by binding to mRNAs and inhibiting their functions (205). Plenty of studies revealed that miRNAs play significant roles, including both oncogenes and tumor suppressors, during the progression and metastasis of lung cancer (206)(207)(208).…”
Section: Microrna (Mirna)mentioning
confidence: 99%
“…They act as gene regulator by binding to mRNAs and inhibiting their functions ( 205 ). Plenty of studies revealed that miRNAs play significant roles, including both oncogenes and tumor suppressors, during the progression and metastasis of lung cancer ( 206 208 ). Overexpression of the let-7 family, miR-486, miR-218, miR-34, and miR-200 were proved to inhibit the tumor cell proliferation, invasion and colony formation, though there is no specific article describing their relations with tumor cells bone migration ( 209 212 ).…”
Section: Other Potential Biomarkersmentioning
confidence: 99%
“…On the other hand, TEXs can also indirectly transfer tumor antigen to antigen presenting cells, like DCs, and then activate the cytotoxic activity of CD8 + T cells and CD4 + T helper cells, so as to inhibit tumor growth [58] . Additionally, the enrichment of HSPs on TEXs such as Hsp70, can stimulate the activity of NK cells [59] and macrophages [60] , and induce MHC class I-restricted cytotoxic T cells activation [61] . Tumor cell-derived exosomal miR-770 could suppress M2 macrophage polarization via targeting MAP3K1, which in turn decreased NSCLC tumor growth [62] .…”
Section: Immunostimulatory Effect Of Texsmentioning
confidence: 99%
“…Tumor cell-derived exosomal miR-770 could suppress M2 macrophage polarization via targeting MAP3K1, which in turn decreased NSCLC tumor growth [62] . Tetraspanins on the exosome surface mainly mediate cell adhesion and participate in maintaining the optimal conformation of immune proteins like MHC class II, thus playing an important role in antitumor immunity through exosomal targeting to DCs [61,[63][64][65] .…”
Section: Immunostimulatory Effect Of Texsmentioning
confidence: 99%